'(Im-)proper' members with '(im-)proper' families? – Framing spousal migration policies in Germany. Issue 2 (25th January 2021) - Block, Laura
ABSTRACT: Even more than other types of migration, liberal democracies allow family migration based on the recognition of the individual right to protection of marriage and family of their members. Restricting family migration, which is increasingly happening all over European states in the past two decades, is thus framed within the liberal rights paradigm. The article critically scrutinises the discursive strategies and categories of policy-makers in Germany employed to justify restricting spousal migration 2005–2010. Following the logic of a 'liberal discursive constraint', restrictive policies infringing upon the right to family protection are introduced and legitimised by political actors not by questioning or qualifying the right as such, but rather by constructing certain categories of 'improper' marriages and 'improper' members. Especially by co-opting the issue of gender equality, Muslim minorities in Germany are discursively positioned outside of the supposedly liberal national community and thus the infringement upon the protection of marriage and family is justified.